Analisis Kesulitan Belajar Matematika Tentang Operasi Hitung Campuran Kelas III SDN Tanjung Mas Semarang - Alifbatati, Firdaayu; Patonah, Siti; Sundari, Riris Setyo (Pena Edukasia, 2023)
This research was conducted to find out the difficulties experienced by class III students of SD Negeri Tanjung Mas Semarang when solving mixed arithmetic operations questions related to concepts, facts, and principles. This can be seen from the results of the recapitulation of students' difficulties in working on questions that the highest percentage of students' difficulties in performing arithmetic operations reached 90%. To overcome these difficulties, the researchers provide several alternatives, namely creating learning innovations that are more creative, so that they can increase students' understanding of mathematics lessons, while during lessons, it is good for educators to provide simple tests so that students are accustomed to planning problem solving in mathematics lessons, difficulties in solving problems that exist in the questions can be overcome by providing simpler questions so that they are easily understood by students and training students so that every time they finish working on a problem to check the answer again whether it is correct or something is wrong.